Transient Neonatal Hyperparathyroidism Unfolding a Noteworthy Cause: A Series of Four Cases - AO Vinitha; VH Sankar; Rahul Aswathy; Karun Arjun; T Alex Sherrin (Journal of Clinical and Diagnostic Research)
Transient Neonatal Hyperparathyroidism (TNHP) is an abnormal bone disorder caused by impaired maternal-foetal calcium transport across the placenta, leading to inadequate foetal bone mineralisation. It is caused by mutations in the gene encoding the Transient Receptor Potential Channel, Subfamily V, Member 6 (TRPV6), which is involved in maternal-to-foetal calcium transport. The TRPV6 mutation results in hypocalcaemia in the foetus, leading to skeletal deformities such as narrow chest walls, multiple rib fractures, bowing of long bones, and generalised osteopenia. Babies are usually born with respiratory distress that requires ventilatory support due to a pliable chest wall. The skeletal abnormalities closely resemble those of osteogenesis imperfecta, skeletal dysplasias and congenital rickets. All four cases described in this series presented with clinical features of undermineralisation of bone and chest wall deformities resembling congenital rickets or osteogenesis imperfecta. One case of suspected osteogenesis imperfecta was found to have a homozygous variant in the TRPV6 gene upon genetic testing. The other three cases presented with respiratory distress after birth and had homozygous variants in the same gene (TRPV6). In newborns, similar clinical presentations coupled with the presence of hyperparathyroidism should raise suspicion of TNHP. Genetic studies may reveal homozygous or compound heterozygous variants in the TRPV6 gene. There will be significant clinical improvement with treatment using oral calcium, as the intestinal transport of calcium becomes effective after birth. Early identification of this transient condition is helpful for timely management.